The Tutor and Tutor Competency With Students Writing Skills - M. Arifin Zaidin; Aco Karumpa (South Sulawesi Education Development (SSED), 2021)
This study aims was to examine of the correlation between tutors and tutors competence with the results of the students writing skills of the distance learning Open University Makassar. This research was ex post facto research. The populations were 387 and the samples were 100. The samples were taken multistage random sampling technique. The data were questionnaire and documentation study of the final semester examinations score. The results demonstrate that (1) there was a positive and significance correlation between tutors (Y = 11.463 + 1.157X1) with R Square of 55,2%. This means that 55.2% of the variation which occurred in the results of the writing skills can be explained by variation of tutors through regression equation Y = 11.463 + 1.157 X1. (2) there was a positive and significance correlation between of tutors’ competence Y = 21,986 + 0,354X2 with R Square 57,6%. It means that 57.6% of the variation occurs on the results of the quality of writing skills can be explained by variations in the tutors’ competence through regression equation, Y = 21,986 + 0,354X2. (3) there was a positive and significant correlation between of tutors and tutors’ competence with Freg = 42.827 and R Square was 71.7%.